UTILIZATION OF PICTURE CARD MEDIA IN EARLY CHILDHOOD LEARNING AT SEKAR LOLIPOP KINDERGARTENACADEMIC YEAR 2023/2024 - Maydio Tegar Rama Bongso (JOETAL: Journal of Education, Teaching and Learning, 2025)
This study aims to explore the use of picture card media in early childhood learning at Sekar Lolipop Kindergarten, Praya, in the 2023/2024 academic year. The focus is on providing opportunities for students to learn from real objects, especially through the use of picture card media. The research method used is a descriptive qualitative approach, with the research location at Sekar Lolipop Kindergarten, Praya. Data were obtained through the principal, teachers/educators, and students, with data collection procedures in the form of observation, interviews, and documentation. Data analysis was carried out using data reduction techniques, data presentation, and drawing conclusions or verification. The results of the study showed that the introduction of the natural environment was carried out in accordance with the guidelines in the kindergarten, such as RPPH and RPPM. Learning is carried out in the open air by utilizing picture cards to get to know jobs and visits to other kindergartens. Teachers implement this activity through introduction, core, and closing, where they introduce the natural environment to children. The use of picture card media in learning provides variation and makes learning more interesting, because it uses real objects around children, such as cards and pictures. This makes learning more interactive and not monotonous.